Influência de diferentes agentes de fixação na resistência de união, por tração, de ligas metálicas fixadas à dentina. - Adabo, Gelson Luis [UNESP]; da Silva Filho, F. P.; de Sá, D. N.; Rettondini, W. C.; dos Santos Cruz, C. A. (My University, 1990)
They were casted pieces using three kinds of alloy (Ni-Cr, Ag-Sn and Cu-Al) with circular and smooth surface. They were cemented to human teeth, on occlusal surface, grounded at dentin level, through three different materials kind (zinc polycarboxylate cement, glassionomer cement and composite). After 24 hours storing, the samples were subjected to the tensile test. The results showed that the samples cemented with composite and the casts made with Ag-Sn alloy had higher bond strength.
Influence of different bonding agents on traction resistance of metal alloys to dentin
Keywords: dental alloy; glass ionomer; Panavia EX; phosphate; polycarboxylate cement; tooth cement; cementation; comparative study; dentin; tensile strength; Cementation; Comparative Study; Dental Alloys; Dental Bonding; Dental Cements; Dentin; English Abstract; Glass Ionomer Cements; Phosphates; Polycarboxylate Cement; Tensile Strength